Метод быстрого поиска фрагмента аудиозаписи с усовершенствованной оценкой меры близости - Ткаченко, А.Н.; Грийо Тукало, О.Ф. (Управляющие системы и машины, 2015)
Предложен метод быстрого поиска неизвестного аудиофрагмента в корпусе аудиозаписей с усовершенствованной оценкой степени близости, позволяющий повысить достоверность результатов поиска. Вследствие применения усовершенствованной оценки степени близости между неизвестным аудиофрагментом и аудиозаписями, содержащимися в корпусе, существенно увеличен уровень различимости собственной аудиозаписи. Запропоновано метод швидкого пошуку невідомого аудіофрагмента в корпусі аудіозаписів з удосконаленою оцінкою міри близькості, що дозволяє підвищити достовірність результатів пошуку. В результаті застосування вдосконаленої оцінки міри близькості між невідомим аудіофрагментом і аудіозаписами, які містяться в корпусі, істотно збільшено рівень розрізнення власного аудіозапису. The development of the Internet, digital media, multimedia technologies and new ways of processing audio information generates enormous interest and attention to the ways in which information technology can be applied. With access to the huge archives of multimedia, virtually anywhere and at any time, it is necessary to propose the new ways to navigate and interact with these large audio archives. This paper proposes a method for the fast search of the unknown audio fragment in the corpus of audio recordings with the improved estimation of the measure proximity, thus enhancing the reliability of the audio search. Through the use of the improved estimation of the measure proximity between the unknown fragment and the audio recordings contained in the corpus, the level of distinguishability of its own audio recording is significantly increased. Experimental results show that the overall distance to its own audio on average 8 times higher than estimate distances to other audio recordings in the corpus.